Associations of Wnt5a expression with liver injury in chronic hepatitis B virus infection - Xiang-Fen Ji; Qi Zhou; Jing-Wei Wang; Fei Sun; Shuai Gao; Kai Wang (BMC Infectious Diseases, 2023)
Abstract Background Aberrant Wnt5a expression contributes to immunity, inflammation and tissue damage. However, it remains unknown whether Wnt5a is associated with liver injury in chronic hepatitis B virus (HBV) infection. We aimed to explore the potential role of Wnt5a expression in liver injury caused by chronic HBV infection. Methods Wnt5a mRNA levels in peripheral blood mononuclear cells (PBMCs) were analyzed in 31 acute-on-chronic hepatitis B liver failure (ACHBLF) patients, 82 chronic hepatitis B (CHB) patients, and 20 healthy controls using quantitative real-time polymerase chain reaction. Intrahepatic Wnt5a protein expression from 32 chronic HBV infection patients and 6 normal controls was evaluated by immunohistochemical staining. Results Wnt5a mRNA expression was increased in CHB patients and ACHBLF patients compared to healthy controls and correlated positively with liver injury markers. Additionally, there was a significant correlation between Wnt5a mRNA expression and HBV DNA load in all patients and CHB patients but not in ACHBLF patients. Furthermore, intrahepatic Wnt5a protein expression was elevated in chronic HBV infection patients compared to that in normal controls. Moreover, chronic HBV infection patients with higher hepatic inflammatory grades had increased intrahepatic Wnt5a protein expression compared with lower hepatic inflammatory grades. In addition, the cut-off value of 12.59 for Wnt5a mRNA level was a strong indicator in predicting ACHBLF in CHB patients. Conclusions We found that Wnt5a expression was associated with liver injury in chronic HBV infection patients. Wnt5a might be involved in exacerbation of chronic HBV infection.